Development of Al-Mu’awwidhah computing for personal data protection against abnormal attacks - Shamsudin, Ahmad Faizul; Ibrahim, Jamaludin; Sembok, Tengku Mohd; Noordin, Mohamad Fauzan; Hashim, Jamil; Wan Yusof, Wan Sabri (2013)
Personal data is constantly being compromised not just by the normal identity thefts but also abnormal attacks. The Islamic concept of Al-Mu’awwidhah inspired the discovery of non-parametric cryptographs for personal data protection against abnormal (paranormal and asymmetric) cyber-attacks. A continuous search on new paradigm of non- parametric cryptographs led to the discovery of ethno-mathematics for substitution block-cipher boxes. The objects based on extracted Al-Qur’an and Al-Hadith symbols by use of ethno-mathematical functions. The extracted objects were insufficient to build the 256 bit block-ciphers. The development of expanding objects from Aramaic, Hebrew, Chinese, Hindu and other symbols are found to fill the gap but only up to216bit out of the 256 bit block-cipher. Initial tests for algebraic attacks indicate Al-Mu’awwidhah Block Cipher resistance to be better than the random parameteic Khazad and Annubis Block Ciphers.